Plasminogen Activator Inhibitor Type I Controls Cardiomyocyte Transforming Growth Factor-β and Cardiac Fibrosis. Issue 7 (15th August 2017) - Flevaris, Panagiotis; Khan, Sadiya S.; Eren, Mesut; Schuldt, Adam J. T.; Shah, Sanjiv J.; Lee, Daniel C.; Gupta, Sweta; Shapiro, Amy D.; Burridge, Paul W.; Ghosh, Asish K.; Vaughan, Douglas E.
Abstract : Background: Fibrosis is the pathological consequence of stress-induced tissue remodeling and matrix accumulation. Increased levels of plasminogen activator inhibitor type I (PAI-1) have been shown to promote fibrosis in multiple organ systems. Paradoxically, homozygous genetic deficiency of PAI-1 is associated with spontaneous age-dependent, cardiac-selective fibrosis in mice. We have identified a novel PAI-1-dependent mechanism that regulates cardiomyocyte-derived fibrogenic signals and cardiac transcriptional pathways during injury. Methods: Cardiac fibrosis in subjects with homozygous mutation in SERPINE-1 was evaluated with late gadolinium-enhanced cardiac magnetic resonance imaging. A murine cardiac injury model was performed by subcutaneous infusion of either saline or Angiotensin II by osmotic minipumps. We evaluated blood pressure, cardiac function (by echocardiography), fibrosis (with Masson Trichrome staining), and apoptosis (with TUNEL staining), and we performed transcriptome analysis (with RNA sequencing). We further evaluated fibrotic signaling in isolated murine primary ventricular myocytes. Results: Cardiac fibrosis was detected in 2 otherwise healthy humans with complete PAI-1 deficiency because of a homozygous frameshift mutation in SERPINE-1 . In addition to its suppressive role during spontaneous cardiac fibrosis in multiple species, we hypothesized that PAI-1 also regulates fibrosis during cardiac injury. Treatment of young PAI-1 −/− mice with Angiotensin II induced extensive hypertrophy and fibrotic cardiomyopathy, with increased cardiac apoptosis and both reactive and replacement fibrosis. Although Angiotensin II-induced hypertension was blunted in PAI-1 −/− mice, cardiac hypertrophy was accelerated. Furthermore, ventricular myocytes were found to be an important source of cardiac transforming growth factor-β (TGF-β) and PAI-1 regulated TGF-β synthesis by cardiomyocytes in vitro as well as in vivo during cardiac injury. Transcriptome analysis of ventricular RNA after Angiotensin II treatment confirmed that PAI-1 deficiency significantly enhanced multiple TGF-β signaling elements and transcriptional targets, including genes for extracellular matrix components, mediators of extracellular matrix remodeling, matricellular proteins, and cardiac integrins compared with wild-type mice. Conclusions: PAI-1 is an essential repressor of cardiac fibrosis in mammals. We define a novel cardiomyocyte-specific regulatory mechanism for TGF-β production by PAI-1, which explains the paradoxical effect of PAI-1 deficiency in promoting cardiac-selective fibrosis. Thus, PAI-1 is a molecular switch that controls the cardiac TGF-β axis and its early transcriptional effects that lead to myocardial fibrosis. Abstract : Supplemental Digital Content is available in the text.